A Development Dilemma: How Does Energy Poverty Improvement Affect Fossil Fuel Energy Consumption in Southeast Asian Countries in the 21st Century? - Thongtai, Chanon; Kanchomphu, Raweeroj (Asian Journal of Applied Economics, 2025)
Governments worldwide have actively addressed energy poverty through extensive subsidy policies; however, these efforts face the complex challenge of balancing improved energy access with long-term sustainable development goals. This study examines the effects of energy poverty improvement (EPI) on fossil fuel consumption using a cubic form of the Environmental Kuznets Curve in five Southeast Asian countries—Philippines, Indonesia, Malaysia, Thailand, and Vietnam—over 2000–2020, employing GLS panel regression. A new EPI indicator is constructed by combining binary data on access to clean cooking energy and rural electricity. Results reveal a non-linear relationship: fossil fuel consumption per capita increases with EPI until a peak value of 91.88, after which it declines, supporting the EKC hypothesis. The findings underscore the need for policies promoting renewable energy adoption to ensure that gains in energy access are consistent with environmental sustainability.